Cholesterol metabolism shapes immune low-response states in LUAD: a multi-omics cholesterol metabolism signature predicts immunotherapy benefit and identifies DHCR7 as a therapeutic target - Du, Mingjun; Zheng, Jianan; Zhou, Guangyao; Zhuang, Yu; Huang, Chenjun; Ye, Wei (Frontiers in Immunology, 2025)
BackgroundCholesterol metabolism has been shown to affect the tumor microenvironment in various cancers, but its immunological role in lung adenocarcinoma (LUAD) remains unclear.MethodsWe integrated 1,682 LUAD samples (including 7 treatment-naïve bulk cohorts and 3 immunotherapy bulk cohorts) to develop a Cholesterol Metabolism Signature (CMS) based on cholesterol metabolism-associated genes. Survival analysis, ROC curves, and PCA were used to evaluate the ability of CMS to predict prognosis and immunotherapy efficacy. Immune infiltration analysis, single-cell transcriptomics, as well as in vitro and in vivo experiments were further performed to investigate the function and mechanism of the key CMS gene, DHCR7.ResultsCMS effectively predicted the survival outcomes and immunotherapy benefits of LUAD patients, which was consistently validated in all independent cohorts. Patients with high CMS had worse prognosis. Compared with 51 previously published LUAD signatures, CMS showed higher predictive accuracy and stratification ability. Immune-related analyses showed that the high CMS group had reduced immune cell infiltration and suppressed immune function, which was further supported by single-cell analysis revealing enhanced immunosuppressive pathways. Expression of the key gene DHCR7 was highly correlated with CMS score (R = 0.42, P<0.05), negatively associated with many immune-related genes and immune cycles, and promoted poor prognosis and cancer pathways. Multiplex immunohistochemistry confirmed that regions with high DHCR7 expression had fewer infiltrating CD8T and CD20B cells. In vitro experiments demonstrated that silencing DHCR7 inhibited the proliferation, invasion, and migration of LUAD cells; mouse models confirmed that suppressing DHCR7 enhanced the efficacy of PD-1 inhibitors. Flow cytometry showed that DHCR7 knockdown significantly increased IFN-γ+CD8T and GZMB+CD8T cell infiltration.ConclusionOur study demonstrates that the CMS can effectively predict prognosis and immunotherapy response in LUAD. DHCR7, as a key gene in CMS, is closely related to immune suppression and poor prognosis. Inhibition of DHCR7 can improve the tumor immune microenvironment and enhance the efficacy of immunotherapy, suggesting that DHCR7 is a potential new target for LUAD immunotherapy.